2011
DOI: 10.1016/j.jjcc.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between clinical outcomes and unintentional pulmonary vein isolation during substrate ablation of atrial fibrillation guided solely by complex fractionated atrial electrogram mapping

Abstract: CFAE-ablation terminates AF without isolating PVs in a high percentage of patients, and yields excellent clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
1
16
4
Order By: Relevance
“…After 1 year of the follow-up period and only a single procedure, 65% of their patients remained arrhythmia free (11%) with antiarrhythmic drug. Iriki et al's [26] findings are in sharp contrast with those of Dibase et al [25]. The factors underlying the differences in both acute and long-term outcomes between these two studies and ours are more likely to be many which will be discussed later below.…”
Section: Studies In Paroxysmal Af Patients: Is Cfae Targeting Ablatiocontrasting
confidence: 79%
See 4 more Smart Citations
“…After 1 year of the follow-up period and only a single procedure, 65% of their patients remained arrhythmia free (11%) with antiarrhythmic drug. Iriki et al's [26] findings are in sharp contrast with those of Dibase et al [25]. The factors underlying the differences in both acute and long-term outcomes between these two studies and ours are more likely to be many which will be discussed later below.…”
Section: Studies In Paroxysmal Af Patients: Is Cfae Targeting Ablatiocontrasting
confidence: 79%
“…After a 1-year follow-up period, only 12% of the patients who received CFAE ablation alone were free of recurrent AF/AT with no antiarrhythmic drugs compared to 74% and 76% in the PVI and PVI with CFAE ablation respectively. By contrast Iriki et al [26] reported excellent outcomes in 54 PAF patients who underwent CFAE ablation alone: Conversion of AF to sinus rhythm could be achieved in this study in 98% of the 54 patients during ablation without DC cardioversion; 30% of the patients, however, received Nikefalant (a class III antiarrhythmic drug) meaning that 68% AF terminated by ablation without drug. Furthermore, in the Iriki et al [26] study the investigators also examined whether PVs were isolated and interestingly only 8% of the PV were unintentionally isolated implying that the success of their procedures were not due to isolation of the pulmonary veins.…”
Section: Studies In Paroxysmal Af Patients: Is Cfae Targeting Ablatiocontrasting
confidence: 64%
See 3 more Smart Citations